Disease-causing mutations of RhoGDIα induce Rac1 hyperactivation in podocytes - Auguste, David (Small GTPases, 2016)
Nephrotic syndrome (NS) describes a group of kidney disorders in which there is injury to podocyte cells, specialized cells within the kidney's glomerular filtration barrier, allowing proteins to leak into the urine. Three mutations in ARHGDIA, which encodes Rho GDP dissociation inhibitor α (GDIα), have been reported in patients with heritable NS and encode the following amino acid changes: ΔD185, R120X, and G173V. To investigate the impact of these mutations on podocyte function, endogenous GDIα was knocked-down in cultured podocytes by shRNA and then the cells were re-transfected with wild-type or mutant GDIα constructs. Among the 3 prototypical Rho-GTPases, Rac1 was markedly hyperactivated in podocytes with any of the 3 mutant forms of GDIα while the activation of RhoA and Cdc42 was modest and variable. All three mutant GDIα proteins resulted in slow podocyte motility, suggesting that podocytes are sensitive to the relative balance of Rho-GTPase activity. In ΔD185 podocytes, both random and directional movements were impaired and kymograph analysis of the leading edge showed increased protrusion and retraction of leading edge (phase switching). The mutant podocytes also showed impaired actin polymerization, smaller cell size, and increased cellular projections. In the developing kidney, GDIα expression increased as podocytes matured. Conversely, active Rac1 was detected only in immature, but not in mature, podocytes. The results indicate that GDIα has a critical role in suppressing Rac1 activity in mature podocytes, to prevent podocyte injury and nephrotic syndrome.